LES TROIS FRONTIERES DE MAIDAN - DE ANGELIS, Christina (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
Maidan, the central square in Kiev, is not just a place but also a movement and a representation of the different borders that exist in the country. Maidan symbolises the historic and political border between Ukraine and Russia. It is also the manifestation of the ideological border between the people and those in power that is at the centre of all civil resistance movement. And finally, Maidan highlights the border between the different factions in Ukraine, between “us” and “them”. This research analyses Maidan as a place, a movement and a symbol using the film by Lostitsa by the same name.